2022
DOI: 10.3389/fpsyg.2022.896231
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Grit Among Working Adults: A Transpersonal Psychology Perspective

Abstract: Positive psychology has paved the way for newer and more informed ideas of living a meaningful, integrated and well-rounded quality of living. The current era of the pandemic has also moulded the ways in which individuals perceive their quality of life and how they want to integrate a holistic approach towards their well-being. The workplace settings have seen tremendous changes in terms of how employers, employees and the organisations at large function and operate. The pre-pandemic concept of success has shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…Park and Cho (2019), also reported the relationship between these two variables in a sample of 239 Korean nurses. Likewise, other more recent research reported the significant effect of Grit on job satisfaction in 209 Indian professionals (Agrawal et al, 2022).…”
Section: Job Satisfactionmentioning
confidence: 80%
“…Park and Cho (2019), also reported the relationship between these two variables in a sample of 239 Korean nurses. Likewise, other more recent research reported the significant effect of Grit on job satisfaction in 209 Indian professionals (Agrawal et al, 2022).…”
Section: Job Satisfactionmentioning
confidence: 80%
“…Tere are no missing data due to the settings of the web-based survey. First, to examine the efect of common method deviation that may arise from the measurement method regarding self-reported scales and can lead to inaccurate results [82,83], Harman's single-factor tests were conducted on all items of the four scales [84]. Te participants' sociodemographic characteristics and major variables were analyzed as descriptive statistics (i.e., mean and standard deviation (SD)).…”
Section: Discussionmentioning
confidence: 99%
“…In Sufism, this transformation process is based on self-purification and the search for divine closeness. In contrast, in Transpersonal Psychology, attention focuses on expanding consciousness and transpersonal realization (Agrawal, 2022). However, these two approaches complement and inform each other at their core, demonstrating that proper growth and self-understanding come through exploring inner depths connected to universal qualities (Sotillos, 2022).…”
Section: Integration Of Sufism and Transpersonal Psychologymentioning
confidence: 99%